Answer:
1. x= 3y+6/2
y=2/3x-2
2.x=−y+3
y=−x+3
Explanation:
1. Let's solve for x.
y=2/3x-2
Step 1: Flip the equation.
2/3x-2=y
Step 2: Add 2 to both sides.
2/3x-2+2=y+2
2/3x=y+2
Step 3: Divide both sides by 2/3.
2/3x/2/3=y+2/2/3
x= 3y+6/2
Let's solve for y.
y=2/3x-2
2. Let's solve for x.
y=−x+3
Step 1: Flip the equation.
−x+3=y
Step 2: Add -3 to both sides.
−x+3+−3=y+−3
−x=y−3
Step 3: Divide both sides by -1.
-x/-1=y-3/-1
x=−y+3
Let's solve for y.
y=−x+3
here are two graphs if you need a better explanation
HOPE THIS HELPS